ISLAM DENGAN PENDEKATAN SAINS KONSTRUKSI INTEGRALITAS ILMU, TEKNOLOGI DAN AGAMA - Niar, Asniar Tanjung (UIC (Universitas Islam Cirebon), 2024)
Science occupies a very crucial position in the world of education. Not only at the level of epistemology, it is even an explanation of an ontological concept which is manifested in the form of thought patterns. Therefore, knowledge cannot come from a cultural institution, human activity, especially in its efforts to know oneself and the natural surroundings. From there it is known that science, technology and culture have a clear relationship structure. All of them are an inseparable series in their role to fulfill human needs. Meanwhile, technology knows